CONSUMER SATISFACTION ANALYSIS OF SEAFOOD PROCESSED PRODUCTS - Rizal, Achmad; Cheung, William; Suryana, Asep Agus Handaka; Nurhayati, Atikah (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
This study aims to determine the attributes that affect the level of customer satisfaction and the value of the level of customer satisfaction in the Bandar Djakarta restaurant of Alam Sutera of Tangerang City. The method used in this study is the method of importance-performance analysis to determine the attributes that affect customer satisfaction and the customer satisfaction index to determine the value of overall customer satisfaction. After all the data has been processed, the data will be analyzed descriptively. The technique used to take samples in this study is accidental sampling. Sampling was carried out for four weeks in July 2019 with a total of 85 respondents. The results of this study indicate that the attributes that make consumers feel satisfied are the variety of food, product taste, food hygiene, safety guarantees, the hospitality of the waitress, queuing time, room comfort and room cleanliness. While the attributes that make consumers feel less satisfied are the cleanliness of eating utensils and the speed at which food is served. The overall value of customer satisfaction is at 85,00.